Pembuatan Web Dashboard Interaktif untuk Analisis Data Penjualan Vending Machine - Ajar Basyar Tsani; Fathoni Mahardika; Deris Santika (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This research aims to develop an interactive web dashboard to support data analysis for vending machine sales. The dashboard is designed to facilitate the management of large datasets through intuitive visualizations and interactive features such as filtering, searching, and pagination. The development process involves several stages, including data collection, data cleaning, analysis, visualization, web design, implementation, and deployment using GitHub Pages. Technologies like HTML, CSS, JavaScript, Chart.js, and Grid.js are utilized to ensure efficiency and accessibility. The results of the research show that the dashboard effectively presents key information, such as sales trends, best-selling products, and payment method preferences, thereby supporting more accurate and data-driven strategic decision-making. However, the research has limitations in integrating predictive analytics. Future development is recommended to include predictive algorithms and test system performance on large-scale data. This solution is expected to contribute significantly to optimizing vending machine management and serve as a development model for similar applications in other business sectors.